Metadata for description of datasets and information resources of Portal Brasileiro de Dados Abertos - Moreira, Fabio Mosso [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP]; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP]; Zafalon, Zaira Regina (Univ Federal Minas Gerais, Escola Biblioteconomia, 2017)
The Brazilian government and the founders of the Open Government Partnership adopted in 2011 the Declaration of Open Government, announcing action plans to make datasets accessible according with the eight principles of Open Government Data, which resulted in the implementation of the Portal Brasileiro de Dados Abertos. Through an information retrieval system, the users can search datasets about health, transportation, public safety, education, government spending and electoral process. Share government data in Web can become a complex activity and the low semantic level of this type of information can causes problems during the search like superficial access and dificult undertanding of datasets. An Efficient description of information resources and an appropriate representation of the datasets can mitigate these problems and contribute to achieving relevant results in the retrieval process. This research brings the question about which elements of metadata are using by government services to represent its information resources. In this sense, the aim of this research is study the process of data sharing in the Portal Brasileiro de Dados Abertos and identifying the metadata used for the representation of datasets.
Keywords: Metadata; Retrieval; Government Data; Dataset; Information Resources